ANALISIS DESKRIPTIF STRUKTUR TEKS PROSEDUR HASIL PEMBELAJARAN PESERTA DIDIK SMP KELAS VIIF - Nur’aini, Anisa; Septiana, Ika; Mukhlis, Mukhlis (Universitas Islam Sumatera Utara, 2023)
The background of this research is that students are still very dependent on teachers and are not used to looking for alternative problem solving independently. The purpose of this study is to analyze and describe the structure of the procedural text on the results of student worksheets in the application of project-based learning models in class VIIF students. The structure of the procedure text that will be described includes the title, objectives, tools and materials and the steps. The method in this research is descriptive qualitative which will later describe the structure of the procedure text on student worksheets. The techniques used in this research are test techniques and non-test techniques. Evidence at the observation stage students are able to make a good title according to the contents of the procedure text steps made, are able to describe the purpose of the procedure text according to the written procedure text, are able to mention tools and materials in full as needed, and are able to mention the steps for using conjunctions, prohibitive sentences, imperative sentences, and solicitation sentences.